Desert sand UHPC and preparation process thereof

By pretreating and modifying desert sand, the problems of low strength and high usage in UHPC production are solved, and UHPC production with high strength, high toughness and high durability are achieved, making full use of desert sand resources.

CN119874278APending Publication Date: 2025-04-25SOUTHWEAT UNIV OF SCI & TECH +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411883869.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-19
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

The existing technology is difficult to effectively utilize desert sand resources, resulting in the problems of high cement, water reducing agent and water consumption, high cracking risk and low strength when producing UHPC.

Method used

High-quality UHPC is prepared by pretreating desert sand, including heating and burning to remove organic matter and part of salt, followed by addition of modified mineral blends and surfactants to improve the surface of the sand and remove harmful components, and by adjusting the proportion of quartz sand and machined sand, high-quality UHPC is prepared.

Benefits of technology

It improves the strength, toughness and durability of desert sand UHPC, reduces water consumption and cracking risks, enhances the adhesion between sand particles and UHPC hardened slurry, and achieves efficient utilization of desert sand resources.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119874278A_ABST
    Figure CN119874278A_ABST
Patent Text Reader

Abstract

The invention discloses desert sand UHPC (Ultra High Performance Concrete) and a preparation process thereof. The desert sand UHPC is prepared from Portland cement, a defoaming agent, mixed sand, an admixture, a water reducing agent and fibers, the UHPC is made of the desert sand and has the performance advantages of being high in strength, toughness and durability, desert sand resources can be fully utilized, the problem that river sand resources are deficient can be solved, and environmental protection is facilitated. According to the desert sand UHPC manufacturing process, desert sand is modified, the defect that the desert sand is low in strength is overcome, the modified mineral admixture and the surfactant are added, components harmful to UHPC can be removed, the surface of sand grains can be improved, and therefore the bonding force between the sand grains and UHPC hardened slurry is enhanced; besides, by adjusting the proportion matching of the quartz sand and the machine-made sand which are the same in grading and different in strength, UHPC of different grades can be produced according to needs, and the method has the advantages of being short in research and development period, short in production burdening time consumption, good in quality control, high in production efficiency and low in cost.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of building materials, and more specifically, to a desert sand UHPC and a preparation process thereof. Background Art

[0002] The distribution of construction sand in my country is uneven, and the reserves are very limited. It cannot be regenerated in a short period of time, and it is difficult to meet the large demand for engineering construction. In addition, the large-scale mining of river sand has also brought serious environmental problems. Although the technology of using sea sand and machine-made sand to replace river sand has achieved certain results, it still faces some problems, and the production capacity cannot meet the growing demand for construction sand. The gap in sand and gravel demand will exist for a long time. How to find a material that can replace natural river sand and meet engineering needs at a low price is a problem that the engineering community is currently facing. How to find a material that can replace natural river sand and meet engineering needs at a low price is a problem that the engineering community is currently facing.

[0003] The infrastructure construction and investment in western my country are increasing and are in a stage of explosive growth. As a key node, the demand for concrete materials and engineering sand in the northwest region has increased sharply. The construction sand in northwest my country is relatively scarce, but it contains huge desert sand resources. At present, the desertified area in my country is about 170km2, accounting for 18.12% of my country's land area. Among them, the northwest region is the most concentrated area of ​​desert in my country, accounting for about 80% of the country's deserts.

[0004] Desert is a barren area with a completely covered sand surface, very few plants, little rain and dry air. China is one of the countries in the world with a large desert area, wide distribution and serious desertification hazards. Traditional desert control and protection methods mainly rely on keeping the land moist and strengthening the moisture retention of the land. The moisture retention is greater than the dryness because it is the most critical factor in reversing desertification. A large amount of water source and maintenance should be the key to reversing desertification. The most effective way to keep the land moist is to provide water and store water and cultivate wind and cold resistant plants and trees. However, this method has high protection and control costs, slow results and is easily reversed. If we take root control and use desert sand as a resource, such as making concrete as a building material, we can greatly improve the effect of preventing desert expansion. It is foreseeable that the rational use of desert sand in the preparation of concrete materials and serving the construction of projects in the region can effectively alleviate the shortage of natural river sand resources and have significant economic benefits and social value. At present, desert sand is mainly used in foundation and roadbed filling, canal slope protection, and ordinary concrete material preparation. Its application range is narrow and the usage is still relatively small.

[0005] UHPC and its components have been vigorously developed in recent years due to their excellent mechanical properties, durability, applicability and economy. They are one of the important fixed materials for construction in high-performance component systems. They are high-performance materials composed of high-performance cementitious materials, early strength aggregates, functional admixtures and additives, and can be widely used in various structural parts and construction scenarios. In conventional UHPC production technology, quartz sand with moderate particle size is generally selected as the fine aggregate of UHPC, while the fineness modulus of desert sand is relatively small, basically less than 1.7, and most of it is less than 0.8, which belongs to the range of ultra-fine sand. If desert sand is directly applied to UHPC without treatment, there will be problems such as high cracking risk and low strength caused by high cement, water reducer and water consumption.

[0006] In view of the above situation, how to utilize desert sand as a resource with higher value to produce high-quality UHPC, broaden the application scenarios of desert sand, and improve the utilization rate of desert sand has become a research topic for many building materials researchers. Summary of the invention

[0007] The invention discloses a desert sand UHPC, which comprises the following raw materials calculated by weight: 28-49 parts by weight of silicate cement, 0.05-0.22 parts by weight of a defoamer, 39-48 parts by weight of mixed sand, 15-40 parts by weight of an admixture, 0.3-0.8 parts by weight of a water reducer, and 1-10 parts by weight of fiber; the mixed sand is prepared by compounding pretreated desert sand, graded quartz sand and graded machine-made sand.

[0008] Preferably, the fineness modulus of the mixed sand is 2.3-2.8; the grading ratio of the pretreated desert sand is 0.075-2.36 mm: 1.18-0.1 mm = 1: (0.2-0.3), and the fineness modulus is 0.5-1.7; the grading ratio of the graded quartz sand and the graded machine-made sand is the same, both of which are 2.36-4.75 mm: 1.18-2.36 mm: 1.18-0.1 mm = 1: (2.8-3.2): (0.5-1), and the fineness modulus is 2.3-3.1.

[0009] Preferably, the silica content of the quartz sand is ≥90%, the mud content is ≤0.5%, and the crushing value is ≤10; the crushing value of the graded machine-made sand is ≤15, and the mud content is ≤0.5%.

[0010] Preferably, the fiber is any one or more of steel fiber, polypropylene fiber, polyacrylonitrile fiber, polyester fiber, JK-7 spiral polyvinyl alcohol fiber, basalt fiber or high polypropylene fiber.

[0011] Preferably, the admixture is S105 mineral powder, SF90 silica ash or Class I fly ash; and the water reducer is TH-928 polycarboxylic acid water reducer with a water reduction rate of ≥40%.

[0012] Preferably, the silicate cement is P·O 42.5 cement.

[0013] A process for preparing desert sand UHPC comprises the following steps:

[0014] Step S1: screening;

[0015] The mixed large-size stones and debris are removed after screening, so that the particle size range of all the final particles is within the distribution range of 0.075-2.36mm;

[0016] Step S2: heating;

[0017] Natural gas is used to heat and burn desert sand at a temperature of 600-1000 degrees Celsius, passing through a three-stage preheater, a homogenizing kiln and a reactor to remove organic matter and some salts in the desert sand;

[0018] Step S3: chemical composition analysis and processing;

[0019] According to the analysis results of the inorganic salt analyzer, the salts are treated by adding corresponding substances;

[0020] Step S4: adding modified mineral admixtures and admixtures;

[0021] Adding an appropriate amount of modified mineral admixtures and surfactants can chemically remove and physically fix most of the harmful components of desert sand to UHPC, improve the surface of sand particles, and enhance the bonding strength between sand particles and UHPC hardening slurry;

[0022] Step S5: compounding the mixed sand;

[0023] The pre-treated desert sand, graded machine-made sand and graded quartz sand pre-treated in the above steps are mixed in a certain proportion, and separated, adjusted and mixed by a T-Sepax high-efficiency three-separation powder separator;

[0024] Step S6: UHPC molding;

[0025] Pre-dry mix the silicate cement, mixed sand, admixtures and water reducer for 1 to 2 minutes at a stirring speed of 90 to 180 r / min. Then add water and defoaming agent for wet mixing. The wet mixing time should not be less than 5 minutes, until the mixture is close to the target fluidity. Then slowly add the fiber. After all the fiber has been added, continue stirring for at least 2 minutes until the fiber is evenly dispersed in the mixture. The total stirring time should be controlled within 20 minutes.

[0026] Preferably, in step S4, the modified mineral admixture is any one or more of zeolite powder, metakaolin, bentonite or silicomanganese slag.

[0027] Preferably, in step S4, the surfactant is a mixture of component A and component B; the component A is any one or more of neutral oxidized rosin resin sodium, sodium salt of alkyl aryl sulfonate with C12 or lignin sulfonate; the component B is any one or more of a silane coupling agent series, a titanate coupling agent series or an aluminate coupling agent series.

[0028] Preferably, in step S5, the fineness modulus of the mixed sand is adjusted by a T-Sepax high-efficiency three-separation powder separator to a cumulative residue of 0-10% on a 5.00 mm sieve, a cumulative residue of 0-25% on a 2.50 mm sieve, a cumulative residue of 10%-50% on a 1.25 mm sieve, a cumulative residue of 41%-70% on a 0.63 mm sieve, a cumulative residue of 70%-92% on a 0.315 mm sieve, and a cumulative residue of 90%-100% on a 0.16 mm sieve.

[0029] The desert sand UHPC of the present invention is prepared from silicate cement, defoamer, mixed sand, admixture, water reducing agent and fiber; by using desert sand to make UHPC, and having the performance advantages of high strength, high toughness and high durability, it can not only make full use of desert sand resources, but also solve the problem of scarce river sand resources, which is conducive to saving resources and energy, and improving the effect of preventing desert expansion. The desert sand UHPC production process of the present invention solves the disadvantage of low strength of desert sand by modifying desert sand. The addition of modified mineral admixtures and surfactants helps to remove harmful components to UHPC and improve the surface of sand particles, thereby enhancing the bonding force between sand particles and UHPC hardened slurry; in addition, by adjusting the proportion of quartz sand and machine-made sand of the same grade and different strengths, different grades of UHPC can be produced according to needs, which has the advantages of short R&D cycle, less time-consuming production and batching, good quality control, high production efficiency and low cost. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] In order to more clearly illustrate the technical solutions in the embodiments of the present invention, the following briefly introduces the drawings required for use in the description of the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.

[0031] Figure 1 The figure is a schematic diagram of a process of desert sand UHPC and its preparation process according to the present invention. DETAILED DESCRIPTION

[0032] The invention discloses a desert sand UHPC and a preparation process thereof. The desert sand UHPC has better working performance, mechanical properties and durability than the desert sand UHPC produced by the prior art, meets the construction requirements of various structural components, and reflects the application value of desert sand resources.

[0033] The following is a clear and detailed description of the technical solutions in the embodiments of the present invention in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0034] The invention discloses a desert sand UHPC, which comprises the following raw materials calculated by weight: 28-49 parts by weight of silicate cement, 0.05-0.22 parts by weight of a defoamer, 39-48 parts by weight of mixed sand, 15-40 parts by weight of an admixture, 0.3-0.8 parts by weight of a water reducer, and 1-10 parts by weight of fiber; the mixed sand is prepared by compounding pretreated desert sand, graded quartz sand and graded machine-made sand.

[0035] UHPC (Ultra-High Performance Concrete) is ultra-high performance concrete. UHPC has extremely high compressive strength, tensile strength and excellent durability, and can maintain stable performance in various extreme environments. High strength: The compressive strength of UHPC can usually reach more than 150MPa, which is much higher than the compressive strength of ordinary concrete. This means that structures built with UHPC can withstand greater pressure and load, greatly improving the safety and stability of the structure. High durability: Due to the dense microstructure of UHPC, its impermeability, freeze-thaw resistance, chemical corrosion resistance and other properties are better than ordinary concrete. This enables UHPC to maintain good performance for a long time in harsh natural environments and extend the service life of the structure. High toughness: By adding steel fibers or synthetic fibers, the tensile strength of UHPC has been significantly improved. This enables UHPC to show better ductility and toughness when subjected to external forces, reducing the risk of structural damage due to brittle fracture. Excellent working performance: UHPC has good fluidity, is easy to cast and form, and has a fast hardening speed, shortening the construction period. At the same time, the self-compacting property of UHPC allows it to achieve a high density without vibration, which improves construction efficiency. UHPC and its components have been vigorously developed in recent years due to their excellent mechanical properties, durability, applicability and economy, and are one of the important fixing materials for construction in high-performance component systems.

[0036] The desert sand UHPC of the present invention makes its microstructure more compact by precisely controlling the proportions of various raw materials, thereby improving its mechanical properties. By adopting the three-sand combination technology of pre-treated desert sand that has been removed and modified in advance, graded quartz sand, and graded machine-made sand, harmful and useless substances in the sand are quickly and effectively removed. At the same time, for sands with different grading ratios, a mixed sand with stable grading can be obtained after a processing system process. The tensile strength and toughness of UHPC are improved by introducing fibers. These fibers form a stable three-dimensional network structure in UHPC, which effectively prevents the expansion and extension of cracks. Compared with UHPC prepared with traditional single-category sand, the desert sand UHPC of the present invention is significantly improved in working performance, mechanical properties and durability.

[0037] Preferably, the fineness modulus of the mixed sand is 2.3-2.8; the grading ratio of the pretreated desert sand is 0.075-2.36 mm: 1.18-0.1 mm = 1: (0.2-0.3), and the fineness modulus is 0.5-1.7; the grading ratio of the graded quartz sand and the graded machine-made sand is the same, both of which are 2.36-4.75 mm: 1.18-2.36 mm: 1.18-0.1 mm = 1: (2.8-3.2): (0.5-1), and the fineness modulus is 2.3-3.1. The traditional mode is to produce different grades of premixes by adjusting the ratio of different admixtures, the ratio of cement dosage and admixtures, the ratio of ultra-fine sand and medium-grade sand (such as quartz sand), and the ratio of admixtures and cementitious materials (cement, admixtures). This has the disadvantages of long research and development time, long production and batching time, low quality control and production efficiency, and high cost. In this embodiment, different grades of UHPC can be produced by adjusting the ratio of medium-grade sand (quartz sand and machine-made sand) of the same grading and different costs.

[0038] Preferably, the silica content of the quartz sand is ≥90%, the mud content is ≤0.5%, and the crushing value is ≤10; the crushing value of the graded machine-made sand is ≤15, and the mud content is ≤0.5%.

[0039] Preferably, the fiber is any one or more of steel fiber, polypropylene fiber, polyacrylonitrile fiber, polyester fiber, JK-7 spiral polyvinyl alcohol fiber, basalt fiber or high polypropylene fiber. The microscopic damage mechanism of UHPC mainly includes micropores, microcracks, grain boundary sliding and slip bands. In order to reduce microscopic damage and improve the mechanical properties of UHPC, the density of UHPC should be increased and the interface transition zone should be strengthened. Experiments show that as the volume content of steel fiber increases, the compressive strength also increases. This is because the number of steel fibers increases, the spacing between fibers becomes smaller, the bridging effect of the fibers is better, and there will be more fibers to inhibit the development of microcracks. UHPC with steel fibers has improved the compressive strength, flexural strength, impact resistance and wear resistance of the newly formed surface layer.

[0040] Furthermore, the steel fiber can be a copper-plated steel fiber, and preferably a copper-plated steel fiber with a length of 13 mm, a diameter of 0.2 mm, a tensile strength of 2930 MPa, and a bending performance pass rate of 95% is used as the manufacturing material of the desert sand UHPC in this embodiment.

[0041] Preferably, the admixture is S105 mineral powder, SF90 silica ash or Class I fly ash; and the water reducer is TH-928 polycarboxylic acid water reducer with a water reduction rate of ≥40%.

[0042] Preferably, the silicate cement is P·O 42.5 cement.

[0043] A process for preparing desert sand UHPC comprises the following steps:

[0044] Step S1: screening;

[0045] The mixed large-size stones and debris are removed after screening, so that the particle size range of all the final particles is within the distribution range of 0.075-2.36mm;

[0046] Step S2: heating;

[0047] Natural gas is used to heat and burn the desert sand at a temperature of 600 to 1000 degrees Celsius, passing through a three-stage preheater, a homogenizing kiln and a reactor to remove organic matter and some salts in the desert sand. This step uses natural gas as fuel, which is widely available and has relatively environmentally friendly combustion products. It will not produce compounds that affect the properties of the desert sand after secondary reaction with the desert sand.

[0048] Step S3: chemical composition analysis and processing;

[0049] According to the analysis results of the inorganic salt analyzer, the salts are treated by adding corresponding substances;

[0050] Step S4: adding modified mineral admixtures and admixtures;

[0051] Adding an appropriate amount of modified mineral admixtures and surfactants can chemically remove and physically fix most of the harmful components of desert sand to UHPC, improve the surface of sand particles, and enhance the adhesion between sand particles and UHPC hardening slurry; by adding modified mineral admixtures and surfactants in this step, the purpose of producing high-strength and high-impermeability UHPC is achieved.

[0052] Step S5: compounding the mixed sand;

[0053] The pre-treated desert sand, graded machine-made sand and graded quartz sand that have been pre-treated in the above steps are mixed in a certain proportion, and sorted, adjusted and mixed by the T-Sepax high-efficiency three-separation powder separator; the amount of ordinary machine-made sand varies depending on the strength grade of UHPC, and the higher the grade, the lower the amount, mainly for the purpose of improving the grading of mixed sand and adjusting the strength grade of UHPC. Since this step, the grading, particle shape, strength, chemical stability, durability and other aspects of the sand have been enhanced.

[0054] After the above steps, the desert sand, graded quartz sand and graded machine-made sand three-sand combination technology is used to quickly and effectively remove harmful and useless substances in the sand. At the same time, for sands with different grading ratios, after the treatment system process, a stable graded mixed sand can be obtained. Since the grading of sands in different regions and different formations is very different, the application scenarios are broad. Use in UHPC. Compared with UHPC prepared with traditional single-category sand, the working performance, mechanical properties and durability are significantly improved.

[0055] Step S6: UHPC molding;

[0056] Pre-dry mix the silicate cement, mixed sand, admixtures and water reducer for 1 to 2 minutes at a stirring speed of 90 to 180 r / min. Then add water and defoaming agent for wet mixing. The wet mixing time should not be less than 5 minutes, until the mixture is close to the target fluidity. Then slowly add the fiber. After all the fiber has been added, continue stirring for at least 2 minutes until the fiber is evenly dispersed in the mixture. The total stirring time should be controlled within 20 minutes.

[0057] Due to the pursuit of UHPC with excellent performance, the water consumption in the traditional UHPC production process is very low. The use of single-material graded sand requires more cementitious materials. The slurry has high viscosity and high admixture dosage, which leads to construction difficulties, defoaming difficulties, higher air content than the design standard, and even bleeding, resulting in problems such as low actual strength and appearance defects after molding. For some structures with high technical difficulty, the fluidity and strength of conventional UHPC cannot meet the design requirements, resulting in high-performance UHPC requiring high-quality admixtures or admixtures or aggregates (natural river sand, lake sand or river sand) to achieve. Although the existing improved technology has improved the traditional technology in terms of product performance, most of the high-cost materials used are used, which makes no contribution to economic efficiency. If desert sand is directly applied to UHPC without treatment, there will be problems such as high cracking risk and low strength caused by high cement, water reducer and water consumption. According to the sampling and testing of sand samples from major deserts across the country, the statistical results of the properties of desert sand are summarized as follows:

[0058] The apparent density of desert sand is 2570-2732kg / m3, which can meet the requirement of apparent density>2500kg / m3 for construction sand. The bulk density is 1400-1595kg / m3, which is close to the bulk density of river sand and basically meets the bulk density requirement of sand for concrete.

[0059] Desert sand has a low mud content, which meets the standard of JGJ55 "Ordinary Concrete Mix Design Code" that the mud content of sand used is less than 3.0% (mass fraction);

[0060] The porosity of desert sand is generally higher than that of river sand, and is basically distributed in the range of 40% to 48%. The fineness modulus of desert sand is relatively small, and is basically less than 1.7, and most of it is less than 0.8, which belongs to the range of ultra-fine sand.

[0061] Desert sand has strong water absorption and a large amount of water is required when preparing concrete. In order to ensure the workability of the mixture, it is necessary to use a composite admixture mainly composed of high-performance water reducers to reduce water consumption and ensure the quality of UHPC.

[0062] In this preparation process, the desert sand is pretreated and improved to address the above shortcomings of the desert sand, and then the improved desert sand is made into UHPC with excellent performance. This improves the existing technology and realizes the resource utilization of desert sand to solve environmental problems. This preparation process mainly uses two directions to treat desert sand UHPC:

[0063] First, desert sand has the characteristics of smooth surface, fine particles, unsatisfactory gradation, large water demand, and low self-strength. In order to make up for the low strength of desert sand and the low bonding strength between cement stone and sand caused by its smooth surface, the existing technology adopts a large amount of cement, but this method will reduce the fluidity of concrete mixture and increase the risk of cracking. In order to make up for the unsatisfactory gradation and high water demand of desert sand, the existing technology adopts the addition of air entraining agent. Although it has a great effect on the fluidity of concrete mixture, the addition of air entraining agent will reduce its mechanical properties and durability.

[0064] This preparation process adopts the technology of pre-treating desert sand, and removes some components in desert sand that cause the desert sand to have a large water demand through heating and burning technology. After heating and burning, unstable organic matter and salt compounds in desert sand are partially volatilized, and some stable compounds are attached to the surface of sand and some decomposition products react with the compounds of minerals contained in sand (compounds such as oxides, nitrates or sulfides are formed on the surface, thereby changing the surface morphology and size and increasing the roughness.) So that the surface roughness of sand is increased, and the increase in the surface roughness of sand is conducive to the bonding strength between sand and cement stone of UHPC. Then, the desert sand is modified by surfactant modifier to solve the problem of smooth surface of desert sand, so that the bonding strength between modified desert sand and cement stone is increased to prepare high-strength and impermeable UHPC. By adding modified mineral admixtures, the problem of unsatisfactory grading of desert sand is solved, and the water demand of modified desert sand is reduced, so as to increase the fluidity of desert sand UHPC.

[0065] Secondly, desert sand has the characteristics of fine particles, single gradation, and low inherent strength. The existing technology adopts the composite use of ultra-fine sand and medium sand (quartz sand) to increase the amount of cement to ensure the strength of UHPC. Then, by adjusting the ratio of ultra-fine sand and medium sand (quartz sand), the ratio of different admixtures, the ratio of cement dosage and admixtures, and the ratio of admixtures and cementitious materials (cement, admixtures), different grades of UHPC are produced. In this way, various grades of UHPC have the disadvantages of long research and development time, long production and batching time, low quality control and production efficiency, and high cost.

[0066] This process prepares UHPC by combining desert sand (improving the particle size distribution of mixed sand to enhance the filling effect), quartz sand (good particle shape and high strength), and machine-made sand (general particle shape but high roughness, good adhesion to the slurry, general strength, and adjusting the strength grade of the UHPC after molding by controlling the mixing ratio). By combining the advantages of the three types of sand and adjusting the ratio of quartz sand and ordinary machine-made sand, different grades of UHPC can be produced quickly and easily.

[0067] Through the above process improvement, the existing technology is improved and the resource utilization of desert sand is realized to solve the environmental protection problem. The desert sand UHPC produced by the preparation process of the present invention has significantly improved working performance, mechanical properties and durability compared with the UHPC premix prepared with traditional single-category sand and conventional admixtures.

[0068] It should be pointed out that the use of river sand from other regions to produce and manufacture UHPC has been widely used. However, the reserves of river sand from other regions are not as good as those of desert sand, and the use of other river sand often damages the ecological environment, while the resource utilization of desert sand improves the ecological environment. The quality stability of other ultra-fine sands is not as good as that of desert sands. The frequency of debugging of the compounding process of different production batches is relatively high, and the cost of purchasing raw materials is high. Unmodified ultra-fine sand can be combined with particularly high-quality admixtures to produce high-performance UHPC. The preparation process provided by the present invention is precisely aimed at improving the inherent defects of desert sand. Using this preparation process, high-quality UHPC can be produced, which greatly alleviates the dilemma of insufficient supply of other river sands, improves the utilization rate of desert sand resources, and also protects the ecological environment of the desert.

[0069] Preferably, in step S4, the modified mineral admixture is any one or more of zeolite powder, metakaolin, bentonite or silicomanganese slag. The addition of the modified mineral admixture optimizes the particle gradation of the cementitious material, achieves the most effective filling effect, and has a lubricating effect to improve the fluidity of UHPC.

[0070] Preferably, in step S4, the surfactant is a mixture of component A and component B; the component A is any one or more of neutral oxidized rosin resin sodium, sodium salt of alkyl aryl sulfonate with C12 or lignin sulfonate; the component B is any one or more of a silane coupling agent series, a titanate coupling agent series or an aluminate coupling agent series.

[0071] In this step, the coupling process through the coupling component in the surfactant is a 4-step reaction model, namely:

[0072] First, the SiX group connected to the silicon atom is hydrolyzed to generate SiOH; then, Si-OH dehydrates and condenses to generate Si-OH-containing oligosiloxane; then, SiOH in the oligosiloxane forms a hydrogen bond with OH on the surface of the substrate; finally, during the heating and curing process, it forms a covalent bond with the substrate accompanied by a dehydration reaction. It is generally believed that only one of the three silanol groups generated by the hydrolysis of the silane coupling agent on the interface is bonded to the surface of the substrate; the remaining two Si-OH groups either condense with Si-OH in other silanes or are in a free state.

[0073] Therefore, silane coupling agents can couple the interface of two materials with very different properties, thereby improving the performance of composite materials and increasing the bonding strength, and obtaining new composite materials with excellent performance and reliability. Silane coupling agents are widely used in rubber, plastics, adhesives, sealants, coatings, glass, ceramics, metal anticorrosion and other fields. Now, silane coupling agents have become one of the indispensable additives in the materials industry.

[0074] The coupling agent has two groups with different properties. The inorganic-philic group can react with the chemical groups on the surface of inorganic materials (such as glass, fly ash and other silicon-containing materials) to form a strong chemical bond; the organic-philic group can react or physically entangle with organic molecules, so that the interface between organic and inorganic materials can be chemically bonded, greatly improving the bonding strength. Experiments show that coupling agents can also "couple" two inorganic materials. Marble was painted with silane coupling agent KH-570, and then cement slurry was applied. Macro-mechanical properties tests were conducted, and the splitting strength was measured to increase by 57% to 84%. Others applied silane coupling agent KH-570 solution on the surface of mortar and granite, and then added new mortar. The results showed that the tensile strength could be increased by 38% and 23% respectively compared with that without coupling agent. This shows that a large number of chemical bonds may have been generated in the interface layer. The strength of desert sand soaked in silane coupling agent KH-570 can also be increased by 13 to 31 compared with that of unsoaked sand.

[0075] Preferably, in step S5, the fineness modulus of the mixed sand is adjusted by a T-Sepax high-efficiency three-separation powder separator to a cumulative residue of 0-10% on a 5.00 mm sieve, a cumulative residue of 0-25% on a 2.50 mm sieve, a cumulative residue of 10%-50% on a 1.25 mm sieve, a cumulative residue of 41%-70% on a 0.63 mm sieve, a cumulative residue of 70%-92% on a 0.315 mm sieve, and a cumulative residue of 90%-100% on a 0.16 mm sieve.

[0076] The following is described through multiple embodiments:

[0077] Example 1

[0078] Step S1: screening; removing the mixed large-size stones and debris after screening, so that the particle size range of all the final particles is within the distribution range of 0.075 to 2.36 mm;

[0079] Step S2: heating; using natural gas to heat and burn the desert sand at a temperature of 600 to 1000 degrees Celsius, passing through a three-stage preheater, a homogenizing kiln and a reactor to remove organic matter and some salts in the desert sand;

[0080] Step S3: chemical composition analysis and processing; adding corresponding substances to the salts for processing according to the analysis results of the inorganic salt analyzer;

[0081] Step S4: adding modified mineral admixtures and admixtures; adding an appropriate amount of modified mineral admixtures and surfactants can chemically remove and physically fix most of the harmful components of desert sand to UHPC, improve the surface of sand particles, and enhance the bonding force between sand particles and UHPC hardening slurry;

[0082] Step S5: compounding the mixed sand;

[0083] The pre-treated desert sand, graded machine-made sand and graded quartz sand pre-treated in the above steps are mixed in a certain proportion, and separated, adjusted and mixed by a T-Sepax high-efficiency three-separation powder separator;

[0084] Step S6: UHPC molding;

[0085] 28-49 parts by weight of Portland cement, 39-48 parts by weight of mixed sand, 15-40 parts by weight of admixture and 0.3-0.8 parts by weight of water reducer are pre-dry mixed for 1-2 minutes at a stirring speed of 90-180r / min. Then water and 0.05-0.22 parts by weight of defoamer are added for wet mixing. The wet mixing time should not be less than 5 minutes, until the mixture approaches the target fluidity. Then 1-10 parts by weight of fiber are slowly added. After all the fiber is added, stirring should be continued for at least 2 minutes until the fiber is evenly dispersed in the mixture. The total stirring time should be controlled within 20 minutes.

[0086] Embodiment 2:

[0087] Step S1: screening; removing the mixed large-size stones and debris after screening, so that the particle size range of all the final particles is within the distribution range of 0.075mm;

[0088] Step S2: heating; using natural gas to heat and burn the desert sand at a temperature of 600 degrees Celsius, passing through a three-stage preheater, a homogenizing kiln and a reactor to remove organic matter and some salts in the desert sand;

[0089] Step S3: chemical composition analysis and processing; adding corresponding substances to the salts for processing according to the analysis results of the inorganic salt analyzer;

[0090] Step S4: adding modified mineral admixtures and admixtures; adding an appropriate amount of modified mineral admixtures and surfactants can chemically remove and physically fix most of the harmful components of desert sand to UHPC, improve the surface of sand particles, and enhance the bonding force between sand particles and UHPC hardening slurry;

[0091] Step S5: compounding the mixed sand;

[0092] The pre-treated desert sand, graded machine-made sand and graded quartz sand pre-treated in the above steps are mixed in a certain proportion, and separated, adjusted and mixed by a T-Sepax high-efficiency three-separation powder separator;

[0093] Step S6: UHPC molding;

[0094] 28 parts by weight of Portland cement, 39 parts by weight of mixed sand, 15 parts by weight of admixture and 0.3 parts by weight of water reducer are pre-dry mixed for 1 minute at a stirring speed of 90r / min. Then water and 0.05 parts by weight of defoaming agent are added for wet mixing. The wet mixing time should not be less than 5 minutes, until the mixture approaches the target fluidity. Then, 1 part by weight of fiber is slowly added. After all the fiber is added, stirring should be continued for not less than 2 minutes, until the fiber is evenly dispersed in the mixture. The total stirring time should be controlled within 20 minutes.

[0095] Example 3

[0096] Step S1: screening; removing the mixed large-size stones and debris after screening, so that the particle size range of all the final particles is within the distribution range of 1.216mm;

[0097] Step S2: heating; using natural gas to heat and burn the desert sand at a temperature of 800 degrees Celsius, passing through a three-stage preheater, a homogenizing kiln and a reactor to remove organic matter and some salts in the desert sand;

[0098] Step S3: chemical composition analysis and processing; adding corresponding substances to the salts for processing according to the analysis results of the inorganic salt analyzer;

[0099] Step S4: adding modified mineral admixtures and admixtures; adding an appropriate amount of modified mineral admixtures and surfactants can chemically remove and physically fix most of the harmful components of desert sand to UHPC, improve the surface of sand particles, and enhance the bonding force between sand particles and UHPC hardening slurry;

[0100] Step S5: compounding the mixed sand;

[0101] The pre-treated desert sand, graded machine-made sand and graded quartz sand pre-treated in the above steps are mixed in a certain proportion, and separated, adjusted and mixed by a T-Sepax high-efficiency three-separation powder separator;

[0102] Step S6: UHPC molding;

[0103] 38.5 parts by weight of Portland cement, 43.5 parts by weight of mixed sand, 27.5 parts by weight of admixture and 0.55 parts by weight of water reducer are pre-dry mixed for 1.5 minutes at a stirring speed of 135r / min. Then water and 0.14 parts by weight of defoaming agent are added for wet mixing. The wet mixing time should not be less than 5 minutes, until the mixture approaches the target fluidity. Then 5.5 parts by weight of fiber are slowly added. After all the fiber is added, stirring should be continued for not less than 2 minutes, until the fiber is evenly dispersed in the mixture. The total stirring time should be controlled within 20 minutes.

[0104] Example 4

[0105] Step S1: screening; removing the mixed large-size stones and debris after screening, so that the particle size range of all the final particles is within the distribution range of 2.36 mm;

[0106] Step S2: heating; using natural gas to heat and burn the desert sand at a temperature of 1000 degrees Celsius, passing through a three-stage preheater, a homogenizing kiln and a reactor to remove organic matter and some salts in the desert sand;

[0107] Step S3: chemical composition analysis and processing; adding corresponding substances to the salts for processing according to the analysis results of the inorganic salt analyzer;

[0108] Step S4: adding modified mineral admixtures and admixtures; adding an appropriate amount of modified mineral admixtures and surfactants can chemically remove and physically fix most of the harmful components of desert sand to UHPC, improve the surface of sand particles, and enhance the bonding force between sand particles and UHPC hardening slurry;

[0109] Step S5: compounding the mixed sand;

[0110] The pre-treated desert sand, graded machine-made sand and graded quartz sand pre-treated in the above steps are mixed in a certain proportion, and separated, adjusted and mixed by a T-Sepax high-efficiency three-separation powder separator;

[0111] Step S6: UHPC molding;

[0112] 49 parts by weight of Portland cement, 48 parts by weight of mixed sand, 40 parts by weight of admixture and 0.8 parts by weight of water reducer are pre-dry mixed for 2 minutes at a stirring speed of 180r / min. Then water and 0.22 parts by weight of defoaming agent are added for wet mixing. The wet mixing time should not be less than 5 minutes, until the mixture approaches the target fluidity. Then 10 parts by weight of fiber are slowly added. After all the fiber is added, stirring should be continued for not less than 2 minutes, until the fiber is evenly dispersed in the mixture. The total stirring time should be controlled within 20 minutes.

[0113] The desert sand UHPC of the present invention is prepared from silicate cement, defoamer, mixed sand, admixture, water reducing agent and fiber; by using desert sand to make UHPC, and having the performance advantages of high strength, high toughness and high durability, it can not only make full use of desert sand resources, but also solve the problem of scarce river sand resources, which is conducive to saving resources and energy, and improving the effect of preventing desert expansion. The desert sand UHPC production process of the present invention solves the disadvantage of low strength of desert sand by modifying desert sand. The addition of modified mineral admixtures and surfactants helps to remove harmful components to UHPC and improve the surface of sand particles, thereby enhancing the bonding force between sand particles and UHPC hardened slurry; in addition, by adjusting the proportion of quartz sand and machine-made sand of the same grade and different strengths, different grades of UHPC can be produced according to needs, which has the advantages of short R&D cycle, less time-consuming production and batching, good quality control, high production efficiency and low cost.

[0114] The above is a detailed introduction to the desert sand UHPC and its preparation process provided by the present invention. For those skilled in the art, according to the ideas of the embodiments of the present invention, there may be changes in the specific implementation methods and application scopes. In summary, the content of this specification should not be understood as limiting the present invention.

Claims

1. A desert sand UHPC, characterized in that: The invention comprises the following raw materials calculated by weight: 28 to 49 parts by weight of silicate cement, 0.05 to 0.22 parts by weight of defoamer, 39 to 48 parts by weight of mixed sand, 15 to 40 parts by weight of admixture, 0.3 to 0.8 parts by weight of water reducing agent, and 1 to 10 parts by weight of fiber; the mixed sand is prepared by compounding pretreated desert sand, graded quartz sand and graded machine-made sand.

2. The desert sand UHPC according to claim 1, characterized in that: The fineness modulus of the mixed sand is 2.3-2.8; the grading ratio of the pretreated desert sand is 0.075-2.36 mm: 1.18-0.1 mm = 1: (0.2-0.3), and the fineness modulus is 0.5-1.7; the grading ratios of the graded quartz sand and the graded machine-made sand are the same, both of which are 2.36-4.75 mm: 1.18-2.36 mm: 1.18-0.1 mm = 1: (2.8-3.2): (0.5-1), and the fineness modulus is 2.3-3.

1.

3. The desert sand UHPC according to claim 2, characterized in that: The silicon dioxide content of the quartz sand is ≥90%, the mud content is ≤0.5%, and the crushing value is ≤10; the crushing value of the graded machine-made sand is ≤15, and the mud content is ≤0.5%.

4. The desert sand UHPC according to claim 2, characterized in that: The fiber is any one or more of steel fiber, polypropylene fiber, polyacrylonitrile fiber, polyester fiber, JK-7 spiral polyvinyl alcohol fiber, basalt fiber or high polypropylene fiber.

5. The desert sand UHPC according to claim 1, characterized in that The admixture is S105 mineral powder, SF90 silica ash or Class I fly ash; the water reducer is TH-928 polycarboxylic acid water reducer with a water reduction rate of ≥40%.

6. The desert sand UHPC according to claim 1, characterized in that The silicate cement is P·O 42.5 cement.

7. The process for preparing desert sand UHPC according to any one of claims 1 to 6, characterized in that: The following steps are included: Step S1: screening; The mixed large-size stones and debris are removed after screening, so that the particle size range of all the final particles is within the distribution range of 0.075-2.36mm; Step S2: heating; Natural gas is used to heat and burn desert sand at a temperature of 600-1000 degrees Celsius, passing through a three-stage preheater, a homogenizing kiln and a reactor to remove organic matter and some salts in the desert sand; Step S3: chemical composition analysis and processing; According to the analysis results of the inorganic salt analyzer, the salts are treated by adding corresponding substances; Step S4: adding modified mineral admixtures and admixtures; Adding an appropriate amount of modified mineral admixtures and surfactants can chemically remove and physically fix most of the harmful components of desert sand to UHPC, improve the surface of sand particles, and enhance the bonding strength between sand particles and UHPC hardening slurry; Step S5: compounding the mixed sand; The pre-treated desert sand, graded machine-made sand and graded quartz sand pre-treated in the above steps are mixed in a certain proportion, and separated, adjusted and mixed by a T-Sepax high-efficiency three-separation powder separator; Step S6: UHPC molding; Pre-dry mix silicate cement, mixed sand, admixtures and water reducer for 1 to 2 minutes at a stirring speed of 90 to 180 r / min, then add water and defoamer for wet mixing. The wet mixing time should not be less than 5 minutes until the mixture is close to the target fluidity; Then slowly add the fiber, and continue stirring for at least 2 minutes after all the fiber has been added, until the fiber is evenly dispersed in the mixture; The total stirring time should be controlled within 20 minutes.

8. The process for preparing desert sand UHPC according to claim 7, characterized in that: In step S4, the modified mineral admixture is any one or more of zeolite powder, metakaolin, bentonite or silicomanganese slag.

9. The process for preparing desert sand UHPC according to claim 7, characterized in that: In step S4, the surfactant is a mixture of component A and component B; the component A is any one or more of neutral oxidized rosin resin sodium, sodium salt of alkyl aryl sulfonate with C12 or lignin sulfonate; the component B is any one or more of a silane coupling agent series, a titanate coupling agent series or an aluminate coupling agent series.

10. The process for preparing desert sand UHPC according to claim 7, characterized in that: In step S5, the fineness modulus of the mixed sand is adjusted to a cumulative residue of 0% to 10% on a 5.00 mm sieve, a cumulative residue of 0% to 25% on a 2.50 mm sieve, a cumulative residue of 10% to 50% on a 1.25 mm sieve, a cumulative residue of 41% to 70% on a 0.63 mm sieve, a cumulative residue of 70% to 92% on a 0.315 mm sieve, and a cumulative residue of 90% to 100% on a 0.16 mm sieve by a T-Sepax high-efficiency three-separation powder separator.